Delimiting the polymorphic congeners of the genus Oerstedia Quatrefages, 1864 (Nemertea, Hoplonemertea), and descriptions of three new species from the Northwest Pacific - Abato, Jamael C.; Chernyshev, Alexei V.; Hookabe, Natsumi; Tsuyuki, Aoi; Kaushik, Gauri; Kajihara, Hiroshi (Frontiers in Ecology and Evolution, 2024)
Three new species of the monostiliferous hoplonemertean genus Oerstedia Quatrefages, 1864 are herein described using morphological and molecular data—Oerstedia pseudoculata sp. nov., from Akkeshi Bay and Oshoro Bay, Hokkaido, Japan and from Aniwa Bay, Sakhalin, Russia; Oerstedia rugosa sp. nov. from Sagami Bay, Misaki, Kanagawa, Japan and Van Phong Bay, Vietnam; and Oerstedia viridifusca sp. nov. from Manazuru, Kanagawa, Japan. Morphologically, O. pseudoculata sp. nov. can be differentiated from O. oculata only by its bright-orange ocelli visible on both sides of the head, and a proboscis pore opening at the ventral tip of the head. These two sister species repeat each other’s color patterns, a phenomenon that can be explained by Vavilov’s law of homologous series. Oerstedia rugosa sp. nov. can be identified by its carmine or deep-red to brownish-red body with several longitudinal, intertwined white lines or wrinkles running from the head to the posterior body, and by 17–23 vaguely bordered white bands composed of variedly sized dots encircling the body, arranged at irregular interval. Oerstedia viridifusca sp. nov. can be distinguished from other Oerstedia by i) the entire body flecked with minute greenish-brown dots, especially densely on the anterior portion of the dorsal surface, but sparsely on the posterior half of the ventral surface; ii) a collar-like portion encircling the body along the posterior cephalic furrow where the greenish-brown dots are absent; iii) the anterolateral edges of the head lacking the greenish-brown dots; and iv) the ocelli being brownish-orange in color. Oerstedia phoresiae (Kulikova, 1987) is reported for the first time from Japan, in addition to its previous distribution record in Russia and in South Korea. Phylogenetic analyses based on the 16S, 18S, 28S ribosomal RNA, cytochrome c oxidase subunit I, and histone H3 genes show that the new species are true congeners of the genus Oerstedia with O. pseudoculata sp. nov. and O. viridifusca sp. nov. nested within the clade Paroerstediella while O. rugosa sp. nov. in the clade Oerstedia. This taxonomic work emphasizes the importance of DNA barcode sequence in the taxonomy and systematics of the polymorphic congeners of the genus Oerstedia.